2007
DOI: 10.1016/j.ydbio.2007.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional reprogramming of somatic cell nuclei during preimplantation development of cloned bovine embryos

Abstract: While somatic cell nuclear transfer (SCNT) techniques have been successfully implemented in several species to produce cloned embryos and offspring, the efficiencies of the procedures are extremely low, possibly due to insufficient reprogramming of somatic nuclei. Employing GeneChip microarrays, we describe global gene expression analysis of bovine in vitro fertilized (IVF) and SCNT blastocysts as well as respective donor cell lines to characterize differences in their transcription profiles. Gene expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…This led us to speculate that they were a consequence of the inhibition of protein synthesis (CHX) or protein phosphorylation (DMAP), but not because of the abnormal [Ca 2C ] i regimen. On the other hand, in agreement with our previous report (Beyhan et al 2007), U2AF1L2, a gene involved in RNA splicing, was only detected in IVF embryos, indicating that reprogramming of this locus failed in SCNT embryos irrespective of the activation protocol. Although the role of U2AF1L2 in embryonic development has not been investigated, the intrinsic capacity of this gene to affect several cellular processes could lead to potentially serious alterations in the ability of cloned embryos to develop normally.…”
Section: Activation Of Cloned Embryos By Plczsupporting
confidence: 92%
See 1 more Smart Citation
“…This led us to speculate that they were a consequence of the inhibition of protein synthesis (CHX) or protein phosphorylation (DMAP), but not because of the abnormal [Ca 2C ] i regimen. On the other hand, in agreement with our previous report (Beyhan et al 2007), U2AF1L2, a gene involved in RNA splicing, was only detected in IVF embryos, indicating that reprogramming of this locus failed in SCNT embryos irrespective of the activation protocol. Although the role of U2AF1L2 in embryonic development has not been investigated, the intrinsic capacity of this gene to affect several cellular processes could lead to potentially serious alterations in the ability of cloned embryos to develop normally.…”
Section: Activation Of Cloned Embryos By Plczsupporting
confidence: 92%
“…POU5F1, NANOG, and SOX2 have been characterized as important for pluripotency and ICM formation, while the transcription factor CDX2 and the FGF receptor type 2 (FGFR2) have been shown to be expressed specifically in the TE of mouse embryos. We also determined the expression of TRYP8, a gene expressed by somatic cells but not during pre-implantation development of fertilized embryos, and of U2AF1L2, a gene that in a previous study (Beyhan et al 2007) we found discriminated between IVF and SCNT embryos. Blastocyst gene expression was normalized to the exogenous control and then to the total cell number in the embryo, as determined just ] i oscillations in SCNT embryos activated using PLCZ cRNA injection.…”
Section: Embryonic Development Of Cloned Embryos Activated By Plcz Crmentioning
confidence: 99%
“…Interestingly, less than twenty genes are typically deregulated in these embryos, and it is important to identify which gene networks are disrupted (Beyhan et al, 2007). A recent microarray study used Trichostatin A to evaluate the effects of assisted epigenetic modification of NT bovine blastocyst transcriptional profiles.…”
Section: Modeling Cellular Epigenetic Status For Nuclear Transfermentioning
confidence: 99%
“…Large-scale evaluation of the expression of genes [9][10][11][12][13][14] Electron microscopy techniques…”
Section: Conventional and Quantitative Rt-pcrmentioning
confidence: 99%